CXCR4 in breast cancer: oncogenic role and therapeutic targeting - Xu C; Zhao H; Chen H; Yao Q (Dove Medical Press, 2015)
Chao Xu,1,* Hong Zhao,1,* Haitao Chen,1 Qinghua Yao2,3 1First Clinical College of Zhejiang Chinese Medical University, 2Department of Integrated Traditional Chinese and Western Medicine, Zhejiang Cancer Hospital, 3Key Laboratory of Integrated Traditional Chinese and Western Medicine, Zhejiang Cancer Hospital, Hangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Chemokines are 8–12 kDa peptides that function as chemoattractant cytokines and are involved in cell activation, differentiation, and trafficking. Chemokines bind to specific G-protein-coupled seven-span transmembrane receptors. Chemokines play a fundamental role in the regulation of a variety of cellular, physiological, and developmental processes. Their aberrant expression can lead to a variety of human diseases including cancer. C-X-C chemokine receptor type 4 (CXCR4), also known as fusin or CD184, is an alpha-chemokine receptor specific for stromal-derived-factor-1 (SDF-1 also called CXCL12). CXCR4 belongs to the superfamily of the seven transmembrane domain heterotrimeric G protein-coupled receptors and is functionally expressed on the cell surface of various types of cancer cells. CXCR4 also plays a role in the cell proliferation and migration of these cells. Recently, CXCR4 has been reported to play an important role in cell survival, proliferation, migration, as well as metastasis of several cancers including breast cancer. This review is mainly focused on the current knowledge of the oncogenic role and potential drugs that target CXCR4 in breast cancer. Additionally, CXCR4 proangiogenic molecular mechanisms will be reviewed. Strict biunivocal binding affinity and activation of CXCR4/CXCL12 complex make CXCR4 a unique molecular target for prevention and treatment of breast cancer. Keywords: breast cancer, CXCR4, drug target, chemokine, angiogenesis